PEMBERATAN SANKSI PIDANA TERHADAP PELAKU KEKERASAN SEKSUAL TERHADAP ANAK DALAM HUBUNGAN KELUARGA (STUDI PUTUSAN NOMOR 215/PID.SUS/2023/PN JKT. BRT): Aggravation Of Criminal Sanctions Against Perpetrators Of Sexual Violence Against Children In Family Relationships (Study Of Decision Number 215/Pid.Sus/2023/PN Jkt. Brt) - Syifa Sabrina Yuwono; Andi Widiatno (AMICUS CURIAE, 2025)
Sexual violence against children within the family is an increasingly prevalent issue, even when the victims are physically prepubescent and lack adult sexual characteristics. This study identifies problems concerning the psychological, emotional, and social impacts experienced by child victims of sexual violence within the family environment, including fear, trauma, mistrust of others, and feelings of guilt over the incidents. The research employs a normative-descriptive approach, utilizing literature review and analysis of relevant case studies. The findings indicate that victims suffer from physical and psychological trauma, exhibit withdrawn behavior, and experience guilt, exacerbated by social intimidation that blames the child for the incident. Sexual violence within the family not only causes individual harm but also disrupts social relationships and the psychological development of the child in the long term. With the results of the research and conclusion, it was found that legal protection and psychological interventions for child victims are critically needed, alongside increased awareness within families and communities to prevent sexual violence and support the comprehensive recovery of victims.